(untitled) (Baghdad Science Journal, 2022)
Chitinase-3-like 1 protein (YKL-40) is a glycoprotein primarily produced in the arthritic joint and plays a crucial role in inflammatory processes. The aim of the study is to establish the role of YKL-40 as a biomarker for rheumatoid arthritis (RA) compared to proinflammatory biomarkers and disease activity. The study included 58 patients and 18 control. Diseases activity score (DAS-28) and clinical disease activity index (CDAI) were measured. Serum level of YKL-40, tumor necrosis factor-α (TNF-α), interleukin-1B (IL-1β), erythrocyte sedimentation (ESR), rheumatoid factor (RF), C-reactive protein (CRP), and anti-citrullinated protein antibody (ACPA) were assessed. The results showed that the median serum YKL-40 level which was 5.42 ng/ml, the TNF-a level which was 123.6 ng/ml, and the IL-1B level which was 204.365 pg/dl were significantly higher in patients compared to control 3.28 (1.58–4.99) ng/ml, 56.47 (9.38–77.01) ng/ml and 67.887 (15.493–122.689)pg/dl respectively. There was no correlation between serum YKL-40 and disease activity, while there were significant associations observed with TNF-α (r=0.5,p =0.0001) and IL-1β (r=0.41, p=0.001). YKL-40 indicating good levels of RA prediction at 2.47 ng/ml, sensitivity 87.9%, specificity 58.6%, accuracy 78.1%, PPV 80.9%, and NPV 70.8%. In conclusion, a higher level of serum YKL-40 is found in RA patients. The findings from our study suggest a strong association between YKL-40 and the proinflammatory biomarkers. As a result, these biomarkers together might play a role in RA pathogenesis, and YKL-40 may be used as a potential diagnostic biomarker for RA.